Protective effect of Esculetin on myocardial injury induced by doxorubicin - Xu, Fan; Li, Xiao; Yu, Xiaolei (Nepalese Journal of Cancer, 2022)
Objective: To study the protective effect of Esculetin on myocardial injury induced by doxorubicin and explore the mechanism of doxorubicin on myocardial injury in rats. Methods: Doxorubicin (2.5mg/kg) was injected intraperitoneally every other day for 6 times to establish a rat model of myocardial injury. The effects of different doses of Esculetin (10mg/kg & 20mg/kg) on serum myocardial enzymes and myocardial tissue were observed. Results: Doxorubicin significantly increased serum myocardial enzymes and the content of myocardial interstitial collagen fibers in mice. Different doses of Esculetin could reduce myocardial injury in a dose-dependent manner. Conclusion: Esculetin has a protective effect on myocardial injury induced by doxorubicin.